Becoming Creole : nature and race in Belize - Johnson, Melissa A., 1962- (Critical Caribbean studies., 2019)
Becoming Creole explores how people become who they are through their relationships with the natural world, and it shows how those relationships are also always embedded in processes of racialization that create blackness, brownness, and whiteness. Taking the reader into the lived experience of Afro-Caribbean people who call the watery lowlands of Belize home, Melissa A. Johnson traces Belizean Creole peoples' relationships with the plants, animals, water, and soils around them, and analyzes how these relationships intersect with transnational racial assemblages. She provides a sustained analysis of how processes of racialization are always present in the entanglements between people and the non-human worlds in which they live. -- Provided by publisher